2009
DOI: 10.5713/ajas.2009.80528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post Hatch Feed Deprivation on Yolk-sac Utilization and Performance of Young Broiler Chickens

Abstract: An experiment was conducted to study the effect of post-hatch feed deprivation on yolk sac utilization and subsequent performance of young broiler chickens (280) up to 35 days of age. The experimental treatments included access to feed at 8 h intervals after hatch, up to 48 h (0, 8, 16, 24, 32, 40 or 48 h). Water was offered ad libitum to all the groups immediately after placement. Results indicated that chicks with access to feed immediately after hatch used up the residual yolk more quickly. Access to feed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 17 publications
11
49
0
2
Order By: Relevance
“…GALT) is stimulated. Besides the effect of early feed intake on GALT development, some studies showed that early feed intake stimulates the utilization of the yolk (Noy et al, 1996;Bhanja et al, 2009). The yolk is the major source of maternal antibodies for the chick and if the utilization of the yolk is stimulated it can result in better protection against infectious agents in the first few weeks after hatch (Larsson et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…GALT) is stimulated. Besides the effect of early feed intake on GALT development, some studies showed that early feed intake stimulates the utilization of the yolk (Noy et al, 1996;Bhanja et al, 2009). The yolk is the major source of maternal antibodies for the chick and if the utilization of the yolk is stimulated it can result in better protection against infectious agents in the first few weeks after hatch (Larsson et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is expected that yolk nutrients would be utilized more quickly by the fasted than the fed chicks, allowing young chicks to maintain their physiological functions. On the contrary, yolk utilization was more rapid in the fed chicks than the fasted chicks, suggesting that yolk transfer is facilitated by the intestinal motility of fed chicks (Bhanja et al 2009). …”
Section: Ph Growth Responsementioning
confidence: 99%
“…Data on the chemical composition of residual yolk sac (data not presented) revealed a higher lipid and ash, but lower protein content in the residual yolk sac of 24 and 36 h FD chicks as compared to the control chicks. This suggested that protein (not fat) could be a limiting nutrient for the newly hatched chicks (Noy and Sklan 2001;Bhanja et al 2009). The residual yolk contributes to the maintenance of young birds during the first few days after hatching (Anthony et al 1989).…”
Section: Immune Organ Development and In Vivo Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The absorption of nutrients from the yolk sac has been reported to be essential to promote subsequent growth (Murakami et al, 1992;Bigot et al, 2001) and early hatching chicks may have had an advantageous developmental and growth pattern (Lamot et al, 2014) due to earlier absorption of the yolk that has typically represented approximately 10% of total BW at initial hatching (Sklan et al, 2000;Wolanski et al, 2006). Early utilization of the yolk could have produced a metabolically more mature chick that was ready to consume feed and concurrently utilize the remaining residual yolk sac materials (Chamblee et al, 1992;Noy & Sklan, 1998b;Halevy et al, 2003;Tona et al, 2003;Yang et al, 2008;Careghi et al, 2005;Bhanja et al, 2009;Shinde et al, 2015). …”
Section: Yolk Sac Percentagementioning
confidence: 99%